2022
DOI: 10.3390/molecules27072152
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Essential Oil of the New Ukrainian Lavandula angustifolia and Lavandula x intermedia Cultivars Grown on the Same Plots

Abstract: New cultivars of lavender adapted to arid steppe conditions were developed by the Institute of Rice of Ukrainian National Academy of Agrarian Sciences (NAAS). This work is a part of the characterization process of the new cultivars. The chemical composition of the essential oil of the seven new Lavandula angustifolia and eight new Lavandula x intermedia cultivars was investigated and compared. In total, 71 different compounds were identified. Linalool and linalool acetate were the main components in both speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…A recent study from Ukraine identified no less than 70 compounds in the essential oil of L. angustifolia across seven genotypes, with numbers varying between 39–47 compounds per cultivar [ 96 ]. A study from Hungary reported up to 36 compounds in the essential oil from the cultivars ‘Budakalászi’ and ‘Maillette’ [ 72 ].…”
Section: Genotypes Cultivated and Breeding Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Ukraine identified no less than 70 compounds in the essential oil of L. angustifolia across seven genotypes, with numbers varying between 39–47 compounds per cultivar [ 96 ]. A study from Hungary reported up to 36 compounds in the essential oil from the cultivars ‘Budakalászi’ and ‘Maillette’ [ 72 ].…”
Section: Genotypes Cultivated and Breeding Trendsmentioning
confidence: 99%
“…Agronomic factors, such as the genotype used [ 72 , 96 ] and aspects related to the cultivation technology, such as fertilization [ 64 , 65 ] and irrigation [ 35 ], were shown to influence the essential oil obtained from lavender. Some factors are very specific, such as the time of day at harvest [ 5 , 73 ].…”
Section: Summary Of the Factors Influencing Essential Oil Of ...mentioning
confidence: 99%
“…In consequence, the obtained EO is much cheaper than true lavender oil and is often used for counterfeiting true lavender oil. The other names for L. × intermedia are lavandin, Dutch lavender, or bastard lavender [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly yes, if we only consider the perfume industry. Lavandin essential oil is cheaper and has sharper smell notes caused by a higher content of camphor, borneol, and 1,8-cineole [ 2 , 7 , 8 , 9 ]. However, is lavandin EO less valuable than true lavender oil in other non-perfumery applications?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation